Legal personhood - Kurki, Visa A. J. (Cambridge University Press, 2023)
This Element presents the notion of legal personhood, which is a foundational concept of Western law. It explores the theoretical and philosophical foundations of legal personhood, such as how legal personhood is defined and whether legal personhood is connected to personhood as a general notion. It also scrutinises particular categories of legal personhood. It first focuses on two classical categories: natural persons (human beings) and artificial persons (corporations). The discussions of natural persons also cover the developing legal status of children and individuals with disabilities. The Element also presents three emerging categories of legal personhood: animals, nature and natural objects, and AI systems. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 15 Dec 2023).
Keywords: Juristic persons -- Philosophy.; Personalism -- Philosophy.